ANALISIS RISIKO MUSCULOSKELETAL DISORDERS (MSDs) TERHADAP PROSES MATERIAL HANDLING PADA OPERATOR PENGOLAH LIMBAH MENGGUNAKAN METODE RAPID ENTIRE BODY ASSESMENT - Genia Auberta; Agus Edy Pramono (Recent in Engineering Science and Technology, 2024)
: Businesses should never stop trying to include every employee in their operations and never skimp on safety precautions. One of the safety methods in the worker-centered approach implementation is the significance of ergonomics. Typically, material handling phases in production processes include physical labor that demands a lot of operator effort. Handling objects by hand raises the possibility of workplace mishaps, which can lead to musculoskeletal injuries. This study focuses on the different labor postures used for gathering, transferring, and positioning waste as well as the manual handling of waste items up to the shredding area. This study evaluates work postures that may result in symptoms of musculoskeletal diseases using the Rapid Entire Body Assessment (REBA) technique. There are three steps in this process. Prior to lowering the waste bucket to the designated place, gather the trash first, then hoist and carry it till it reaches the mechanical area. Three grades 9, 2, and 6 were obtained from the analysis utilizing the REBA (Rapid Entire Body Assessment) approach. Based on these findings, the first stage has to be improved right away. Thus, in order to meet the improvement objective, we created a telescopic reach that enables employees to change the height a device that aids in bettering workers' posture while picking up trash.